2021
DOI: 10.1001/jamanetworkopen.2021.12837
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Workplace Trauma and Posttraumatic Stress Disorder Among Intern Physicians

Abstract: Key Points Question What is the prevalence of work-related trauma exposure, and what factors are associated with posttraumatic stress disorder among intern physicians? Findings In this cohort study of 1134 interns, 56.4% reported trauma exposure during internship, and 19.0% of those experiencing trauma screened positive for posttraumatic stress disorder. Risk factors for trauma exposure included non-Hispanic White race/ethnicity, more hours worked, early fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Lifetime trauma exposure is prevalent in health care professionals, and clinicians face widespread vicarious workplace trauma that occurs even from the beginning of their careers. 128 A cohort study of intern physicians found that 56.4% of participants reported exposure to trauma in the workplace, 129 and a cross-sectional national survey of surgical residents indicated that PTSD prevalence was more than 3 times that of the general population. 130 Occupational exposure to trauma is continuous and can have deleterious effects on practitioners' personal wellness and patient care outcomes.…”
Section: Survey Item No (%) Of Studies Referencesmentioning
confidence: 99%
“…Lifetime trauma exposure is prevalent in health care professionals, and clinicians face widespread vicarious workplace trauma that occurs even from the beginning of their careers. 128 A cohort study of intern physicians found that 56.4% of participants reported exposure to trauma in the workplace, 129 and a cross-sectional national survey of surgical residents indicated that PTSD prevalence was more than 3 times that of the general population. 130 Occupational exposure to trauma is continuous and can have deleterious effects on practitioners' personal wellness and patient care outcomes.…”
Section: Survey Item No (%) Of Studies Referencesmentioning
confidence: 99%
“…In terms of the differences found in post-traumatic symptoms, physicians seem to be the most affected. The significant difference observed when comparing physicians and other healthcare professionals, which, to our knowledge, has not been investigated in previous studies performed during the COVID-19 pandemic, might be explained by considering the main independent risk factors for post-traumatic disorders in healthcare, which are (i) working on the front line; (ii) being under occupational pressure; (iii) receiving a low level of support from the hospital administration; and (iv) having greater responsibility for frontline clinical care [ 28 , 29 ]. Especially during exceptional events such as the current pandemic, such conditions typically affect frontline healthcare workers, doctors in particular, who, more than the others, have to take on the decision-making responsibility of patients’ lives.…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed a baseline survey 2 months before their residency start, followed by quarterly surveys during the intern year (eAppendix 1 in Supplement 1). The fourth quarterly survey included the adapted Primary Care PTSD Screen for Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) (PC-PTSD-5) …”
Section: Methodsmentioning
confidence: 99%